Headscarves to Die for: Freedom of Choice and a Free- will Symbol in Orhan Pamuk’s Snow - Sri Hariyatmi (Indonesian Journal of English Language Studies (IJELS), 2020)
This article intends to unfold Orhan Pamuk’s conception or how he (re) presents women and their headscarves within Islamic tradition, with particular reference to his novel Snow. Snow opens with the return of Ka, a Turkish exile who has been leaving his country for 12 years to Istanbul in order to attend his mother’s funeral. He then decides to investigate a wave of suicide by young girls in the provincial city of Kars who object the ban of hijab in public spaces. This study discovers that Pamuk explores the lamentation of the Muslim women emanating out of the domain of religion and the will of the state as a stepping-stone to re (claim) the meaning of their headscarf and identity. Grounded in Mahmood theory, this study argued that headscarf has a deeper meaning than just a symbol of religious devotion. It is a platform of Muslim women’s individual will to exercise their chosen identity.